Biofuel Production from Waste Cooking Oils and its Physicochemical Properties in Comparison to Petrodiesel - Lamichhane, Ganesh; Khadka, Sujan; Adhikari, Sanjib; Koirala, Niranjan; Poudyal, Dhruba Prasad (Nepal Journal of Biotechnology, 2020)
Haphazard mining and consumption of fossil fuels have reduced petroleum reserves causing fossil fuel depletion and environmental degradation; thus, reflecting the need for the cheaper, renewable and eco-friendly alternative source of petroleum to meet the fuel demand. A million liters of edible oil used for cooking foods and date expired oils from oil manufacturers are discarded into sewage. This study primarily intends to study the feasibility of biodiesel production using such waste oils. In this work, biodiesel was prepared from waste cooking oils by a process called transesterification with NaOH as a catalyst. Our results showed that methyl ester (biodiesel) (92.67±0.90%), soap materials (1.33±0.224%), and glycerol (6±0.68%) were obtained after the transesterification of waste cooking oil. The physicochemical properties of biodiesel such as density, viscosity, volatility, surface tension, and flashpoint were analyzed, which were found to be 0.862±0.006 g/cm3, 2.23±0.021 cP, 0.327×10-3±4.5×10-6 g/s, 32.03±0.138 dyne/cm, 169.67±0.810°C, respectively. These properties were compared with that of commercial diesel as well as with the values specified by the American Society for Testing and Materials (ASTM) D6751. The density and the surface tension of the biodiesel were found similar to that of petrodiesel but its volatility was 3 times lower. Fourier-transform infrared spectroscopy (FTIR) spectra of the biodiesel showed methyl ester functional group at 1436 cm-1. Based on the cost of the materials used for production, the cost of biodiesel was estimated to be about 81 Nepalese rupees (0.67 USD) per liter. The properties of biodiesel also met the standard values of ASTM D6751. These findings indicate that waste oil is one of the feasible biodiesel sources and it can be used as a suitable alternative to petrodiesel.